2020
DOI: 10.1515/dema-2020-0040
|View full text |Cite
|
Sign up to set email alerts
|

Coefficient inequalities for a subclass of Bazilevič functions

Abstract: AbstractLet f be analytic in {\mathbb{D}}=\{z:|z\mathrm{|\hspace{0.17em}\lt \hspace{0.17em}1\}} with Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The method used applies complex analytical tools in the form of lemmas suitable for verification (Ravichandran & Verma, 2015;Marjono et al, 2017;Thomas, 2017;Fitri et al, 2020). First, the second to fifth coefficients of the strongly convex function are calculated.…”
Section: Methodsmentioning
confidence: 99%
“…The method used applies complex analytical tools in the form of lemmas suitable for verification (Ravichandran & Verma, 2015;Marjono et al, 2017;Thomas, 2017;Fitri et al, 2020). First, the second to fifth coefficients of the strongly convex function are calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Special functions are crucial in several disciplines such as mathematical physics and numerical analysis. A large number of researchers are interested in investigating different special functions from numerical and practical points of view; see, for example, [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…The linearization coefficients of problem (2) were found in terms of a product of two terminating hypergeometric functions of the type 3 F 2 (1) (see [17]). In [34], the authors found closed forms for one or two of the appearing 3 F 2 (1) for some specific choices of the involved parameters, and therefore, some new reduced linearization formulas were developed.…”
Section: Introductionmentioning
confidence: 99%